High-Current Multi-Finger Mesa InGaAs/InP DHBTs - 金智 程伟 苏永波 刘新宇 徐安怀 齐鸣 (Chinese physics letters, 2009)
Characteristics of single- and multi-finger mesa InGaAs/InP double heterojunction bipolar transistors （DHBTs） are compared. The current gain decreases with the increasing number nf of the emitter fingers due to the mutual thermal interaction between the fingers. The Kirk current can be as high as 150mA for four-finger DHBT. No degradation of the peak of the current gain cutoff frequency ft is found for multi-finger DHBTs. The peak of the maximum oscillation frequency fmax decreases with an increase of nf due to the increasing parasitic resistance of the base. The results are very helpful for applications of the common-base DHBTs in power amplifiers operating at very high frequencies.